How to Balance and Integrate Multiple Social Identities: Reading 1 Corinthians - Cornelius, Elma M. (Neotestamentica, 2024)
The focus of this paper is to interpret Paul's reference to and opinion on different social identities in 1 Corinthians and to find an answer, through an interpretation of 1 Corinthians 7, to the question of how to balance and integrate multiple social identities. Relevant passages in 1 Corinthians are interpreted by using an interdisciplinary method, including the fruits of sociological and psychological studies of social identities, while taking the socio-historical background of the text into consideration, interpreting the structure of the letter, considering the use of persuasion strategies and stylistic devices, and undertaking word studies. It is concluded from 1 Corinthians that through God a spiritual identity is possible - an "in-Christ" identity. Paul argues in 1 Corinthians that one's spiritual identity is not supposed to replace other identities. For the sake of unity and peace, one's spiritual identity, with the implication of the transformation of the believer, should infiltrate other social identities.